(untitled) (Journal of Hama University, 2022)
This study aims to investigate the existence of empirical evidence for the effect of momentum on stock returns and the possibility of achieving positive returns by following the momentum strategies tested by Jegadeesh & Titman (1993), and to explain momentum returns in Damascus Stock Exchange, based on historical data represented by a series of daily closing prices for the shares of all companies listed in Damascus Securities Exchange during the period from 1/1/2018 to 31/3/2022. The study concludes that there is a weak effect of momentum, but it is statistically significant, by following six strategies out of sixteen strategies, Strategy (12, 3) achieved the highest average monthly return by 1%. as the results of the research showed that momentum returns is a compensation for systematic risks, while unsystematic risks don’t generate returns, and this is consistent with rational interpretations of momentum, but from a Perspective of behavioral. The theory also showed that stock prices walk randomly , there is no autocorrelation of own stock returns, which indicates that momentum is not caused by behavioral biases or delayed or underreaction of investors, so, momentum in Damascus Securities Exchange cannot be explained Behavioral theory.